Carrier cell-mediated delivery of oncolytic parvoviruses for targeting metastases - Raykov, Zahari Zahariev; Rommelaere, Jean (International journal of cancer, 2004)
Over the last few years, naturally occurring or genetically manipulated oncolytic viruses gained increasing attention as novel therapeutics for cancer treatment. The present work provides proof of principle that an organotropic cell-based carrier system is suitable to deliver oncolytic parvoviruses to a tissue known to be a target for the formation of metastases. Carrier cells were inactivated by γ-irradiation after infection, which was found not to affect the production and release of parvoviruses that were capable of lysing cocultured target neoplastic cells. Although systemically administered parvovirus H-1 showed a pronounced therapeutic effect against the development of established Morris hepatoma (MH3924A) lung metastases, the carrier cell strategy offered a number of advantages. Infected carriers were able to sustain H-1 virus expression for 6 days in the lungs of rats affected by metastatic disease and to reduce the spreading of the virus to peripheral organs. Compared to direct virus injection, the carrier cell protocol led to an improved therapeutic effect (metastases suppression) and a lesser generation of virus-neutralizing antibodies. These data support the use of carrier cells to deliver oncolytic viruses and/or viral vectors locally in tumors and, more particularly, metastases.
Gesehen am 18.02.2021